The Relationship between Sea Water Intrusion and Fresh Water Availability in the Provision of Clean Water Sources in Padang Pariaman Regency West Sumatra Province - Raharini, Hasmy; Razak, Abdul; Diliarosta, Skunda (Balai Publikasi Indonesia, 2025)
The provision of clean water in Indonesia is a people's right guaranteed by the state, especially to meet the minimum daily basic needs for a healthy, clean and adequate quantity, maintained quality and affordable. The availability of fresh water as a source of clean water illustrates the potential for water availability and sustainability. The limited amount of fresh water is a challenge to meet community needs in the form of transportation facilities, toilets for local communities and aquaculture. This condition is also affected by climate change, especially for Indonesia which is in the tropics. The water parameters of the Batang Tapakis River illustrate that the quality of river water is influenced by the people around the river and seawater has entered the river. Community empowerment in providing access to drinking water through community-based activities is a strategic step to overcome the scarcity of fresh water. Participation of the community, government and various related parties can provide reinforcement and commitment so as to achieve the availability of water sources with an insight into sustainable development